Techniques and Tips for Freehand Placement of C7 Pedicle Screws With Respect to Cervicothoracic Constructs: 2-Dimensional Operative Video. Issue 6 (23rd August 2019) - Clifton, William; Edwards, Steve; Louie, Christopher; Dove, Conrad; Damon, Aaron; Nottmeier, Eric; Pichelmann, Mark
Abstract: We present a surgical video highlighting the technical pearls for C7 pedicle screw placement with respect to cervicothoracic constructs. Pedicle screw placement into C7 has been shown to enhance the biomechanical stability of both cervical and cervicothoracic constructs and is safe for patient related outcomes. 1, 2 Rod placement across the cervicothoracic junction is known to be difficult because of the variable starting point of the C7 pedicle screw, which may cause misalignment of the polyaxial heads with respect to the C7 and C6 screw heads. Using our step-wise method of anatomic screw placement, this potential pitfall is minimized. The T1 pedicle screw is placed first. The C6 lateral mass screw starting point is displaced slightly superiorly from the midpoint of the lateral mass in order to make room for the polyaxial head of the C7 pedicle screw. A small laminotomy is performed in order to find the medial border of the C7 pedicle. Palpation of the medial border allows for an approximation of the pedicle limits. The cranial-caudal angle of drilling is perpendicular to the C7 superior facet, and the medial-lateral trajectory typically falls between 15 and 20 degrees medial. Once the pedicle is cannulated, a ball-tipped probe is used to confirm intraosseous position. A rod is cut and contoured to the appropriate length of the construct. The C7 pedicle screw should capture the rod easily with slight displacement of the polyaxial head. Postinstrumentation anteroposterior and lateral fluoroscopy are performed to confirm good position of the lateral mass and pedicle screws. Patient consent was not required for this cadaveric surgical video.